Analisis sikap konsumen terhadap pembelian produk komputer merek Wearnes (Studi Kasus: Mahasiswa Fakultas Ekonomi Universitas Gadjah Mada Yogyakarta) = An Analysis of the Consumer's Attitude toward the Purchase of Wearne - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
The objectives of this research are (1) to identify the effects of the consumer's attitude toward behavior on the consumer's behavioral intention to purchase Wearnes-brand computers in Yogyakarta Regency, (2) to identify the effects of subjective norms on the consumer's behavioral intention to purchase Wearnes-brand computers, (3) to identify the effects of the consumer's attitude tcward behavior together with the subjective norms on the consumer's behavioral intention to purchase Wearnes-brand computers, (4) to measure both variables (attitude toward behavior and subjectivenorms), i.e. which one has greater effects on the consumer's behavioral intention to purchase Wearnes-brand computers. me theoretical model adopted in the research is Fishbein and Ajzen's theory of reasoned action. In this study, however, an external variable, i.e. income variable (Y), was included in the theoretical model.. The sample used in the study consisted of 150 respondents, i.e. students of the Faculty of Economics, Gadjah Mada University. The sample was collected using the purposive and convenience sampling methods. The data were collected through a set of questionnaires. Prior to the distribution of the questionnaires, a pre-survey of the respondents was carried out to identify the attributes and referent groups. Next the validity and reliability. Variables were measured using Thurstone's equal-interval scales. Finally, the data obtained from each variable were analyzed using inferience statistics: simple and multiple regression analysis. The findings of the research showed that